2013
DOI: 10.1128/jb.00988-13
|View full text |Cite
|
Sign up to set email alerts
|

A New Addition to the Cell Plan of Anammox Bacteria: "Candidatus Kuenenia stuttgartiensis" Has a Protein Surface Layer as the Outermost Layer of the Cell

Abstract: bAnammox bacteria perform anaerobic ammonium oxidation (anammox) and have a unique compartmentalized cell consisting of three membrane-bound compartments (from inside outwards): the anammoxosome, riboplasm, and paryphoplasm. The cell envelope of anammox bacteria has been proposed to deviate from typical bacterial cell envelopes by lacking both peptidoglycan and a typical outer membrane. However, the composition of the anammox cell envelope is presently unknown. Here, we investigated the outermost layer of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 74 publications
(95 reference statements)
2
46
0
Order By: Relevance
“…This makes the G.obscuriglobus cell surface similar to those of some Archaea [28] and to those of Gram-positive bacteria where a periplasm appears to exist despite the absence of a Gram-negative wall outer membrane [29], as well as perhaps to another well-studied compartmentalized planctomycete, Kuenenia suttgartiensis , where an S-layer protein wall overlies an outermost membrane [30]. Such Gram-negative bacteria as Caulobacter crescentus also have an outermost proteinaceous layer [31] but it is attached to a lipopolysaccharide-containing outer membrane and in addition they possess a typical peptidoglycan layer between the outer and inner membranes, and conventional bacterial cell division system [32].…”
Section: Discussionmentioning
confidence: 95%
“…This makes the G.obscuriglobus cell surface similar to those of some Archaea [28] and to those of Gram-positive bacteria where a periplasm appears to exist despite the absence of a Gram-negative wall outer membrane [29], as well as perhaps to another well-studied compartmentalized planctomycete, Kuenenia suttgartiensis , where an S-layer protein wall overlies an outermost membrane [30]. Such Gram-negative bacteria as Caulobacter crescentus also have an outermost proteinaceous layer [31] but it is attached to a lipopolysaccharide-containing outer membrane and in addition they possess a typical peptidoglycan layer between the outer and inner membranes, and conventional bacterial cell division system [32].…”
Section: Discussionmentioning
confidence: 95%
“…The proteinaceous barrier was previously suggested to substitute for other classical Gram-negative cell features, such as cell surface protection more typically provided by O antigen (20), a rigid structural framework in place of peptidoglycan (13), and possibly as an attachment platform for degradative enzymes, as in a related species, Rhodopirellula baltica (21). The proteinaceous exterior of G. obscuriglobus has not been shown to constitute a surface layer (S-layer), typically composed of only one or two proteins in a lattice configuration, like that found in some other bacteria, including archaea and the planctomycete "Candidatus Kuenenia stuttgartiensis" (13,22,23). The original cell wall analysis of G. obscuriglobus by Stackebrandt et al (18) found the cell wall composition to include many amino acids, and the ability of the G. obscuriglobus cell to maintain its integrity was demonstrated by the finding that cell sacculi retained their native cell morphology after 10% SDS treatment (18), thus exhibiting resistance to SDS that is more like that of cells that have a peptidoglycan-containing murein sacculus (21).…”
mentioning
confidence: 99%
“…Adapted from reference 30. (35), outer membrane, peptidoglycan-containing periplasm (36), cytoplasmic membrane, cytoplasm, anammoxosome membrane, anammoxosome that contains tubule-like structures (white arrowheads), and electron-dense, iron-rich particles (black arrowheads). Note that not all tubule-like structures visible in the micrograph were visualized in the schematic overview.…”
mentioning
confidence: 99%